2020
DOI: 10.1055/a-1232-4575
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglobulin Antibodies as a Prognostic Factor in Papillary Thyroid Carcinoma Patients with Indeterminate Response After Initial Therapy

Abstract: The clinical outcome of papillary thyroid carcinoma (PTC) patients with an indeterminate response after initial therapy is reported to be intermediate, between incomplete and excellent responses. This study evaluated the outcomes of PTC patients with indeterminate response after initial therapy. It was further determined whether the indeterminate findings predicted outcomes more precisely. Patients were further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Finally, thyroglobulin antibodies, which have been recently suggested for monitoring the course of the disease or as a marker for the outcome, were not elevated or normalized in all patients in this study ( 26 , 27 ), even in the subgroup experiencing disease progress. This should be taken into account, when interpreting the present data.…”
Section: Discussionmentioning
confidence: 47%
“…Finally, thyroglobulin antibodies, which have been recently suggested for monitoring the course of the disease or as a marker for the outcome, were not elevated or normalized in all patients in this study ( 26 , 27 ), even in the subgroup experiencing disease progress. This should be taken into account, when interpreting the present data.…”
Section: Discussionmentioning
confidence: 47%
“…Malandrino et al [12] report 6.9% of structural disease; of note patients with positive TgAb were excluded from both studies. Other authors found higher frequency of structural disease, ranging from 10.6 to 19.5% [8][9][10][11] In the present series, patients with larger primary tumors, high risk of recurrence (as strati ed by ATA) and higher preablation Tg levels had a greater probability of structural/biochemical recurrence at the end of follow-up. Several studies found dynamic risk assessment [6] is a better predictor of structural disease than AJCC/UICC or ATA staging systems [9,[14][15][16]].…”
Section: Discussionsupporting
confidence: 45%
“…This points towards tailoring strategies of follow-up according to the type of IR, with more stringent controls in Tg (+) patients, while avoiding unnecessary procedures in patients with positive TgAb with a stable/descending tendency [20,21]. On the contrary, Landenberger et al reports a greater risk of structural incomplete response in the population of patients with IR due to positive TgAb (31.25% vs 2.63% and 8.3% in the Tg (+) and non-speci c ndings on imaging studies group respectively) [11]. It is relevant to mention that the tendency of TgAb (+) levels in this series was not informed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An indeterminate response may be observed in 12%-23% of the patients with LRPTC, but 80%-90% of them will never experience disease recurrence ( 73 , 74 ). An analysis of stimulated Tg can be helpful in these cases.…”
Section: Follow-up Strategiesmentioning
confidence: 99%